Individual cognitive remediation therapy benefits for patients with anorexia nervosa and high autistic features - Dandil, Yasemin (Eur Eat Disord Rev, 2019)
Cognitive remediation therapy (CRT) is an increasingly implemented intervention in psychiatric conditions. The majority of randomized treatment trials in psychiatry reports cognitive improvements resulting in better functional outcomes in CRT groups. This brief report from the national inpatient treatment programme for eating disorders demonstrates cognitive performance task–based improvements in patients with high and low autistic characteristics. This preliminary study shows feasibility and benefits of individual CRT in patients who have autism spectrum disorder features.